International Adult and Continuing Education Hall of Fame Panel - Juanita Johnson Bailey; Michael Newman; James Pappas; Janet Poley (Adult Education Research Conference, 2015)
There have been major “sea changes” in adult higher education in the time of my career. Significant among those include online and hybrid education, the creation of adult centric and proprietary institutions, the concomitant unbundling of degrees and credentialing, the enormous growth of adult and non-traditional students, the true globalization of American style education and the reduction of adult education departments/tracks and/or their replacement with human resource development. I suggest that we are in a golden era of self-directed adult learning; but, that it is incumbent upon us in adult education to address more directly and with greater energy the impact of each of these trends. The field needs to expand or develop theories and policy that more effectively encompass the influence of academic technology, the use of social media in creating communities of self-directed learners, the changing nature of academia and the profes- sorate and the shaping of the future of adult higher education.